2016
DOI: 10.7314/apjcp.2016.17.1.57
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 MspI Polymorphism and Cervical Carcinoma Risk in the Multi-Ethnic Population of Malaysia: a Case-Control Study

Abstract: Background: Tobacco smoking is considered a risk factor for cervical cancer development due to the presence of tobacco based carcinogenic metabolites in cervical cells of female smokers. In this study, we investigated the role of the T3801C (MspI) polymorphism of CYP1A1, a gene encoding an enzyme necessary for the initiation of tobacco based carcinogen metabolism, on cervical cancer risk. The T to C substitution may alter CYP1A1 activities, potentially elevating cervical cancer risk. Since results of gene-dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
1
14
1
Order By: Relevance
“…The polymorphic status in the m3 locus may be specific for persons of African-American descent (Garte et al, 2001;Li et al, 2004). Our results show a lack of significant association between m1 and m2 polymorphisms and cervical cancer risk, which as in several others tudies-done among Japanese, Israeli Jewish, Polish, Chinese, and Indian populations (Sugawara et al, 2003;Gutman et al, 2009;Roszak et al, 2014;Tan et al, 2016). To contrast, significant associations between m1 and/or m2 polymorphism and increased cervical cancer risk have been documented in several populations (Tan et al, 2017;Juárez-Cedillo et al, 2007;Jain et al, 2017;Li et al, 2016;Wang et al, 2017;Ding et al, 2018), and a meta-analysis indicated that the m1 (CC) genotype was associated with an increased risk for cervical cancer among Asians and Mixed populations (Wu et al, 2013).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The polymorphic status in the m3 locus may be specific for persons of African-American descent (Garte et al, 2001;Li et al, 2004). Our results show a lack of significant association between m1 and m2 polymorphisms and cervical cancer risk, which as in several others tudies-done among Japanese, Israeli Jewish, Polish, Chinese, and Indian populations (Sugawara et al, 2003;Gutman et al, 2009;Roszak et al, 2014;Tan et al, 2016). To contrast, significant associations between m1 and/or m2 polymorphism and increased cervical cancer risk have been documented in several populations (Tan et al, 2017;Juárez-Cedillo et al, 2007;Jain et al, 2017;Li et al, 2016;Wang et al, 2017;Ding et al, 2018), and a meta-analysis indicated that the m1 (CC) genotype was associated with an increased risk for cervical cancer among Asians and Mixed populations (Wu et al, 2013).…”
Section: Discussionsupporting
confidence: 43%
“…To date, genetic polymorphisms of human CYP1A1 have been widely studied for the susceptibility to various cancers (e.g., cancer of lung, oral, larynx, breast, thyroid, prostate, renal, cervix uteri, gastric, and colon) (Li et al, 2004;Gajecka et al, 2005;Little et al, 2006;Siraj et al, 2008;Wright et al, 2010;Li et al, 2016;Balaji et al, 2012;Agudo et al, 2014;Meng et al, 2015). Notwithstanding, to our knowledge there are no recent reports of any association between the four polymorphic loci of the CYP1A1 and cervical cancer susceptibility (Sugawara et al, 2003;Juárez-Cedillo et al, 2007;Gutman et al, 2009;Roszak et al, 2014;Abbas et al, 2014;Tan et al, 2016;Jain et al, 2017). Our aim was thus to evaluate these four polymorphic loci of CYP1A1 for the cervical cancer susceptibility among Northeast Thai women.…”
Section: Research Articlementioning
confidence: 99%
“…The main characteristics of studies included in the meta-analysis are shown in Table 1 . With respect to MspI polymorphism, 13 studies [ 10 13 , 15 18 , 20 , 31 34 ] (2148 cases and 2252 controls) were eligible. What needs illustration is that the study of Tan et al was performed on mixed ethnicity population, after careful assessment and discussion, we classified the Indians as Caucasians and categorized Malay and Chinese as Asian population while performing subgroup analyses.…”
Section: Resultsmentioning
confidence: 99%
“…What needs illustration is that the study of Tan et al was performed on mixed ethnicity population, after careful assessment and discussion, we classified the Indians as Caucasians and categorized Malay and Chinese as Asian population while performing subgroup analyses. [ 34 ] Therefore, 9 studies [ 10 , 15 18 , 20 , 32 34 ] (1323 cases and 1401 controls) were performed on Caucasians, and 5 studies [ 11 13 , 31 ] (825 cases and 851 controls) were performed on Asian population. Concerning Ile462Val polymorphism, 8 studies [ 10 , 12 , 14 , 16 , 18 , 19 , 31 , 32 ] (1466 cases and 1690 controls) were eligible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation